Silver selenide-based composite room-temperature thermoelectric material and preparation method thereof

Amorphous Sb2S3 was synthesized by solvent thermal reaction and room temperature ultrasonic assisted method, and using discharge plasma sintering technology, it was successfully introduced into the Ag2Se matrix to form the Ag2Se/Sb2(S,Se)3 composite material, solving the second phase of amorphous nanometers. The composite problems in thermoelectric materials have achieved efficient optimization of thermoelectric performance.

CN119191348AActive Publication Date: 2024-12-27SICHUAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411320924.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Research on the introduction of amorphous nanosecond phase into thermoelectric materials has not been widely explored, and amorphous materials are prone to crystallization and transformation at high temperatures, making it difficult to recombinate through traditional methods, resulting in difficult optimization of thermoelectric properties.

Method used

Polycrystalline Ag2Se and nanoscale amorphous Sb2S3 were synthesized by solvent thermal reaction and room temperature ultrasonic assisted method. Amorphous nanospinning was uniformly introduced into the Ag2Se matrix by liquid phase recombination method, and Ag2Se/Sb2(S, Se)3 composite thermoelectric material uses the metastable characteristics of amorphous Sb2S3 to react with the Ag2Se matrix to form a second phase of ternary amorphous Sb2(S,Se)3.

Benefits of technology

Thermoelectric performance is significantly optimized. The average ZT value of Ag2Se/Sb2(S,Se)3 composite material is higher than 1, the thermal conductivity is reduced, the carrier concentration and energy band structure are adjusted, and the electron thermal excitation is suppressed, achieving high thermal power optimization. and high average thermoelectric superiority.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191348A_ABST
    Figure CN119191348A_ABST
Patent Text Reader

Abstract

A preparation method of the silver selenide-based composite room-temperature thermoelectric material comprises the following steps: firstly, respectively synthesizing polycrystalline Ag2Se and nanoscale amorphous Sb2S3 through solvothermal reaction and a room-temperature ultrasonic-assisted method, then successfully and uniformly modifying the amorphous nano Sb2S3 on the surface of Ag2Se powder through liquid-phase compounding at room temperature, and finally, preparing the silver selenide-based composite room-temperature thermoelectric material by combining a spark plasma sintering technology, thereby obtaining the silver selenide-based composite room-temperature thermoelectric material. The sintering pressure is 45 MPa, the sintering temperature is 300-380 DEG C, and the block Ag2Se / Sb2 (S, Se) 3 composite thermoelectric material is prepared. In the thermoelectric material, the ternary amorphous Sb2 (S, Se) 3 serves as a second phase, so that phonon scattering is enhanced, the heat conductivity is remarkably reduced, and the thermoelectric material has a relatively high power factor and shows excellent thermoelectric performance; in the temperature range of 300K to 390K, the average ZT value of the Ag2Se / Sb2 (S, Se) 3 composite material is higher than 1 and is obviously superior to that of a pure-phase Ag2Se material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermoelectric materials, in particular to a silver selenide-based composite room-temperature thermoelectric material and a preparation method thereof. Background Art

[0002] The development of the Internet of Things and mobile electronic devices has led to a large demand for self-powered power supplies, miniaturized cooling components, and fast-response temperature sensors. Room-temperature thermoelectric materials have attracted widespread attention due to their potential as key electronic components. In addition, thermoelectric materials have also shown attractive prospects in the recovery of low-grade waste heat, which has further stimulated research on high-performance room-temperature thermoelectric materials. Thermoelectric performance depends on the thermoelectric figure of merit, which is defined as ZT = S 2 σT / κ, where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, T is the absolute temperature of the material, S 2 σ is also called power factor (PF). High-performance thermoelectric materials need to have both high power factor and low thermal conductivity.

[0003] Silver selenide (Ag2Se) is an n-type narrow bandgap semiconductor with high electron mobility, good electrical properties, and ultra-low intrinsic lattice thermal conductivity. It shows good prospects in room temperature thermoelectric applications. The thermoelectric figure of merit ZT of Ag2Se can be effectively improved by means of doping / solid solution, changing the stoichiometric ratio, defect regulation, and composite second phase. Among them, the composite of the appropriate second phase can not only optimize the thermoelectric properties of the material, but also effectively improve the mechanical properties of the material. At present, a variety of materials have been introduced into Ag2Se as the second phase, such as carbon nanotubes, Te, CuAgSe, AgSbSe2, AgAl, etc., but these second phases are all stable crystalline materials. Compared with crystals, because amorphous materials have metastable characteristics, uncontrollable situations may occur in the preparation process of composite amorphous materials. For example, the temperature and pH during the preparation process may cause the amorphous to undergo a crystallization transition, thereby losing the significance of the composite amorphous second phase. Therefore, the research on introducing amorphous second phases into thermoelectric materials has not been widely explored. However, in amorphous materials, the lack of typical long-range order of crystals makes amorphous nanomaterials have some unconventional structural features, such as abundant surface dangling bonds, highly unsaturated coordination, etc. These structural characteristics may cause the modulation of electronic properties, and amorphous nanomaterials show potential for practical applications in the field of thermoelectrics. Therefore, the introduction of amorphous nanosecond phases in thermoelectric materials deserves in-depth understanding and research. Summary of the invention

[0004] In view of the current technical difficulties in introducing amorphous nano second phase values ​​into thermoelectric materials, the present invention provides a silver selenide-based composite room-temperature thermoelectric material and a preparation method thereof. Specifically, the thermoelectric material is an Ag2Se-based material of composite amorphous nano Sb2(S,Se)3.

[0005] Firstly, polycrystalline Ag2Se and nanoscale amorphous Sb2S3 were synthesized by solvothermal reaction and room temperature ultrasound-assisted method, respectively. Then, amorphous nano-Sb2S3 was successfully introduced uniformly into the Ag2Se matrix by liquid phase composite method at room temperature. Bulk Ag2Se / Sb2(S,Se)3 composite thermoelectric material was prepared by combining spark plasma sintering technology.

[0006] The specific preparation method steps of the Ag2Se / Sb2(S,Se)3 composite thermoelectric material are as follows:

[0007] S1. Prepare pure phase Ag2Se powder as follows:

[0008] S11. Dissolve AgNO3 in ethylene glycol, add Se powder, and stir until the Se powder is evenly dispersed in the solution to obtain a dispersion; the molar ratio of AgNO3 to Se powder is 2:1.

[0009] S12, add NaOH solution to the dispersion, stir evenly, heat to 200-250°C, and react for 24 hours.

[0010] S13. After the reaction is completed, the solid product is collected by centrifugation, and the solid product is washed and vacuum dried to obtain pure Ag2Se powder.

[0011] S2. Preparation of amorphous nano-Sb2S3 powder, as follows:

[0012] S21. Dissolve SbCl3 in HCl solution to obtain solution A; dissolve Na2S·9H2O in NaOH solution to obtain solution B; the molar ratio of SbCl3 and Na2S·9H2O is 2:3.

[0013] S22. During continuous ultrasonic oscillation, solution B is slowly added dropwise to solution A, and ultrasonication is continued for 2 hours. The solid product is then collected by centrifugation, and further washed and dried to obtain amorphous nano-Sb2S3 powder.

[0014] S3. Preparation of Ag2Se / Sb2(S,Se)3 composite thermoelectric material, as follows:

[0015] S31. Ultrasonic dispersion of pure Ag2Se powder in acidic water to form Ag2Se dispersion; ultrasonic dispersion of Sb2S3 powder in another portion of acidic water to form Sb2S3 dispersion.

[0016] S32, drop the Ag2Se dispersion into the Sb2S3 dispersion under continuous ultrasonic conditions, then mechanically stir for 2-3 hours, and then let the powder settle, collect the precipitated powder and vacuum dry it at a vacuum drying temperature of 50-70°C for 20-24 hours to obtain Ag2Se / Sb2S3 composite powder. In this step, amorphous nano-Sb2S3 is uniformly modified on the surface of the Ag2Se powder by electrostatic adsorption binding force.

[0017] S33. The Ag2Se / Sb2S3 composite powder is sintered into a block by spark plasma sintering at a sintering pressure of 45 MPa, a sintering temperature of 300-380°C, and a holding time of 5-7 min to finally obtain Ag2Se / Sb2(S,Se)3 composite thermoelectric material.

[0018] Preferably, in step S31, the amount of Sb2S3 powder used accounts for 0.1-0.6% of the mass of pure phase Ag2Se powder.

[0019] Preferably, in step S31, the acidic water used is an aqueous solution adjusted to pH=3.

[0020] Compared with the prior art, the present invention is beneficial in that:

[0021] (1) In the present invention, amorphous Sb2S3 is used as the second phase. Due to its metastable characteristics, S in amorphous Sb2S3 is easily volatilized during spark plasma sintering, resulting in the lack of anions in the second phase. The lack of anions prompts the second phase to react with the anions in the matrix to compensate for the charge, that is, the second phase easily reacts with Se in the Ag2Se matrix; a small amount of Se in the Ag2Se matrix enters the amorphous material to form a ternary amorphous Sb2(S,Se)3 second phase.

[0022] (2) The thermoelectric performance of the thermoelectric material of the present invention is optimized by introducing a ternary amorphous Sb2(S,Se)3 second phase; Sb2(S,Se)3 can adjust the composition of the silver selenide matrix, thereby adjusting the carrier concentration and band structure of the material; the thermal excitation of electrons is suppressed, and Sb2(S,Se)3 can strongly scatter phonons, significantly reducing the thermal conductivity of the material, so that the material obtains a high thermoelectric figure of merit and a high average thermoelectric figure of merit; in the temperature range of 300K to 390K, the average ZT value of the Ag2Se / Sb2(S,Se)3 composite material is higher than 1, which is significantly better than the pure phase Ag2Se material.

[0023] (3) In the prior art, since amorphous materials are prone to crystallization transformation at high temperatures, it is difficult to compound amorphous materials through traditional melting methods, mechanical alloying methods, and one-step solvent thermal methods. The present invention adopts a relatively mild room temperature ultrasound-assisted liquid phase compounding method, utilizing the opposite surface potential characteristics of the two materials to achieve uniform mixing of amorphous Sb2S3 in Ag2Se powder. Subsequently, spark plasma rapid sintering is performed to achieve a chemical reaction between amorphous Sb2S3 and the matrix material Ag2Se, thereby obtaining Ag2Se / Sb2(S,Se)3 composite thermoelectric material.

[0024] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 SEM images of pure phase Ag2Se powder and powder samples of Ag2Se / Sb2(S,Se)3 composite thermoelectric materials, where (a) is pure phase Ag2Se powder and (b) is composite thermoelectric material AS-0.4.

[0026] Figure 2 TEM characterization results of Ag2Se / Sb2(S,Se)3 composite thermoelectric material (AS-0.4), where (a) and (b) are HAADF images and corresponding EDS results, respectively, and (c) and (d) are HRTEM images.

[0027] Figure 3 Performance test data of Ag2Se / Sb2(S,Se)3 composite thermoelectric materials with different Sb2S3 contents, where (a) is the variation of thermal conductivity with temperature in the temperature range of 300-390K; (b) is the Grüneisen parameter diagram; (c) is the variation of ZT value with temperature; (d) is the average ZT value in the temperature range of 300-390K.

[0028] Figure 4 The figure shows the change of ZT value of the composite materials of pure phase Ag2Se (AS-0), Ag2Se composite amorphous Sb2S3 (AS-0.4SS / A) and Ag2Se composite crystalline Sb2S3 (AS-0.4SS / C) with temperature.

[0029] Figure 5 The graph shows the change of thermal conductivity of the composite materials of pure phase Ag2Se (AS-0), Ag2Se composite amorphous Sb2S3 (AS-0.4SS / A) and Ag2Se composite crystalline Sb2S3 (AS-0.4SS / C) with temperature.

[0030] Figure 6The power factor (PF) of the composite materials of pure phase Ag2Se (AS-0), Ag2Se composite amorphous Sb2S3 (AS-0.4SS / A) and Ag2Se composite crystalline Sb2S3 (AS-0.4SS / C) varies with temperature. DETAILED DESCRIPTION

[0031] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0032] Example 1

[0033] A method for preparing Ag2Se / Sb2(S,Se)3 composite thermoelectric material, the steps are as follows:

[0034] S1. Preparation of pure phase Ag2Se powder:

[0035] (1) 45 ml of ethylene glycol was added to a 100 ml polytetrafluoroethylene liner, 1.6987 g of AgNO3 powder was added to the liner, and the liner was placed on a magnetic stirring table and stirred until the AgNO3 was completely dissolved; then 0.3948 g of Se powder was added to the liner, and stirring was continued until the Se powder was evenly dispersed in the solution.

[0036] (2) Add 5 ml of 10 mol / L NaOH solution to the inner liner, continue stirring at room temperature for 15 min, and then transfer the polytetrafluoroethylene inner liner to a stainless steel reactor; move the reactor to a high-temperature oven, set the reaction temperature to 230°C, and set the reaction time to 24 h; after the reaction is completed, turn off the oven power supply, cool the reactor with the oven, and open the reactor when the temperature of the reactor drops to room temperature to take out the inner liner.

[0037] (3) The reaction solution was centrifuged to collect the solid product, and the solid product was washed three times in a high-speed centrifuge using deionized water and anhydrous ethanol respectively; the powder was then placed in a vacuum drying oven and dried at 60°C for 24 hours to obtain pure Ag2Se powder.

[0038] S2. Preparation of amorphous nano-Sb2S3 powder:

[0039] (1) Weigh 0.9124 g of SbCl3 and dissolve it in 48 ml of 4 mol / L HCl solution to obtain solution A. Weigh 1.441 g of Na2S·9H2O and dissolve it in 56 ml of 2 mol / L NaOH solution to obtain solution B.

[0040] (2) During continuous ultrasonic oscillation, solution B was slowly added dropwise to solution A; ultrasonic oscillation was continued for 2 h, and then the solid product was collected by centrifugation. The solid product was washed with deionized water and anhydrous ethanol for 3 times, respectively, and then centrifuged; the product was placed in a vacuum drying oven, set at 80°C, and dried for 12 h to obtain amorphous nano-Sb2S3 powder.

[0041] S3. Prepare Ag2Se / Sb2(S,Se)3 composite thermoelectric materials, respectively control the amount of Sb2S3 to 0.1%, 0.2%, 0.4%, and 0.6% of the mass of Ag2Se, and prepare composite thermoelectric materials with different Sb2S3 contents; the specific method is as follows:

[0042] (1) Weigh 3.6 g of pure Ag2Se powder, disperse it in 90 ml of a pH = 3 aqueous solution, and ultrasonically disperse it for 30 min; weigh Sb2S3 according to the dosage ratio of Sb2S3 and Ag2Se, disperse it in 100 ml of a pH = 3 aqueous solution, and ultrasonically disperse it for 30 min; the pH = 3 aqueous solution is obtained by adding hydrochloric acid to deionized water to adjust the pH.

[0043] (2) The Ag2Se dispersion was slowly dripped into the Sb2S3 dispersion during continuous ultrasound; then the mixture was placed on a magnetic stirring table and vigorously stirred for 2 h; after the stirring was completed, the powder was allowed to settle, and the precipitated powder was collected and washed by centrifugation for 3 times with deionized water and anhydrous ethanol respectively; the powder was placed in a vacuum drying oven, the drying temperature was set at 333 K, and dried for 24 h to obtain Ag2Se-x wt.% Sb2S3 (x = 0.1, 0.2, 0.4, 0.6) composite powders.

[0044] (3) The composite powders with different contents obtained in step (2) are sintered into blocks by spark plasma sintering, and the sintering temperature is set to 350°C, the sintering pressure is 45 MPa, the heating rate is 50°C / min, and the holding time is 5 min. During the sintering process, Sb2S3 reacts with Se in the matrix to form a Sb2(S,Se)3 ternary amorphous composite phase, that is, Ag2Se / Sb2(S,Se)3 composite thermoelectric material is obtained.

[0045] Ag2Se-x wt.%Sb2S3 (x=0.1, 0.2, 0.4, 0.6) composite powders were plasma sintered to prepare Ag2Se / Sb2(S,Se)3 composite thermoelectric materials with different contents, which were abbreviated as AS-0.1, AS-0.2, AS-0.4 and AS-0.6 respectively.

[0046] The pure phase Ag2Se powder prepared in step S1 and the Ag2Se / Sb2(S,Se)3 composite thermoelectric material obtained in step S3 were observed by scanning electron microscope. Figure 1, (a) is a SEM image of pure phase Ag2Se powder (abbreviated as AS-0), and (b) is a SEM image of AS-0.4. It can be seen that the pure phase Ag2Se powder is in micron-sized particles. After the composite treatment in step S3, the surface of the Ag2Se particles has an obvious second phase, and the distribution is relatively uniform, which shows that the method of the present invention successfully achieves uniform composite of Ag2Se and amorphous second phase.

[0047] Figure 2 TEM characterization results of Ag2Se / Sb2(S,Se)3 composite thermoelectric material (AS-0.4) obtained from Ag2Se-0.4%Sb2S3 composite powder. Figure 2 (a) and (b) are the HAADF images and the corresponding EDS results, respectively. It can be seen from the figures that the particle size of the second phase is between 300 and 400 nm, and the three elements Sb, S, and Se are evenly distributed in the second phase. Figure 2 (c) and (d) are HRTEM images, corresponding to Figure 2 The red and blue areas in (a) show that the matrix Ag2Se is in a crystalline state, and the second phase region is amorphous. The above results show that during the spark plasma sintering process of Ag2Se and Sb2S3 composite powder, under the influence of temperature and pressure, the second phase reacts with the matrix to generate a new ternary amorphous second phase Sb2(S,Se)3.

[0048] Figure 3 Performance test data of Ag2Se / Sb2(S,Se)3 composite thermoelectric materials prepared from Ag2Se–x wt.%Sb2S3 (x=0.1, 0.2, 0.4, 0.6) composite powders with different Sb2S3 contents. Figure 3 (a) shows the variation of thermal conductivity of composite materials such as AS-0, AS-0.1, AS-0.2, AS-0.4, and AS-0.6 with temperature in the temperature range of 300 to 390 K. It can be seen that compared with pure Ag2Se powder, the thermal conductivity of Ag2Se / Sb2(S,Se)3 composite thermoelectric materials is significantly reduced. As the Sb2S3 content increases from 0.1% to 0.4%, the thermal conductivity continues to decrease. When it increases to 0.6%, the thermal conductivity increases. This is due to the agglomeration of the second phase and the uneven distribution. Figure 3 (b) is the Grüneisen parameter of composite materials such as AS-0, AS-0.1, AS-0.2, AS-0.4, and AS-0.6. It can be seen that as the Sb2S3 content increases from 0 to 0.6%, γ first increases and then decreases. The size of the Grüneisen parameter (γ) represents the strength of the anharmonicity in the crystal. The larger the γ, the stronger the anharmonicity of the lattice vibration, the stronger the scattering of phonons, and the lower the lattice thermal conductivity. Figure 3The results of (a) and (b) show that the introduction of uniformly distributed Sb2(S,Se)3 in Ag2Se can effectively reduce the thermal conductivity. Figure 3 (c) is the ZT value of composite materials such as AS-0, AS-0.1, AS-0.2, AS-0.4, and AS-0.6 as a function of temperature. It can be seen that compared with pure Ag2Se powder, the ZT value of Ag2Se / Sb2(S,Se)3 composite thermoelectric materials is significantly improved. At 390K, the ZT value of the sample with 0.4% Sb2S3 content is as high as 1.17, which has obvious performance optimization compared with the uncomposite sample. Figure 3 (d) is the average ZT value of composite materials such as AS-0, AS-0.1, AS-0.2, AS-0.4, and AS-0.6 in the temperature range of 300 to 390 K. It can be seen that the average ZT of the sample with a Sb2S3 content of 0.4% is higher than 1, achieving optimization of thermoelectric performance.

[0049] Figure 4 The ZT values ​​of the composite materials of pure phase Ag2Se (AS-0), Ag2Se composite amorphous Sb2S3 (AS-0.4SS / A) and Ag2Se composite crystalline Sb2S3 (AS-0.4SS / C) vary with temperature. The dosage ratio of amorphous Sb2S3 and crystalline Sb2S3 is the same, and their composite dosage accounts for 0.4% of the mass of Ag2Se. Crystalline Sb2S3 is a finished product purchased on the market, and the preparation method of Ag2Se composite crystalline Sb2S3 is the same as step S3 of Example 1. It can be seen from the figure that when the composite ratio of amorphous Sb2S3 and crystalline Sb2S3 is the same, the ZT value of the composite thermoelectric material of Ag2Se composite amorphous Sb2S3 is significantly higher than the thermoelectric material of Ag2Se composite crystalline Sb2S3 and pure phase Ag2Se. However, the ZT value of the thermoelectric material of Ag2Se composite crystalline Sb2S3 is lower than that of pure phase Ag2Se. It can be concluded that compared with crystalline Sb2S3, the composite material formed by amorphous Sb2S3 as the second phase and Ag2Se has excellent and outstanding thermoelectric properties.

[0050] Figure 5 The thermal conductivity of the composite materials of pure Ag2Se (AS-0), Ag2Se composite amorphous Sb2S3 (AS-0.4SS / A) and Ag2Se composite crystalline Sb2S3 (AS-0.4SS / C) varies with temperature in the temperature range of 300-390K. It can be seen that the thermal conductivity of the composite thermoelectric material of Ag2Se composite amorphous Sb2S3 is the lowest, which is significantly lower than the thermoelectric material of Ag2Se composite crystalline Sb2S3 and pure Ag2Se. This further shows that compared with crystalline Sb2S3, the composite material formed by the composite of amorphous Sb2S3 and Ag2Se has better thermoelectric properties.

[0051] Figure 6 The power factor (PF) of the composite materials of pure phase Ag2Se (AS-0), Ag2Se composite amorphous Sb2S3 (AS-0.4SS / A) and Ag2Se composite crystalline Sb2S3 (AS-0.4SS / C) varies with temperature in the temperature range of 300-390K. It can be seen that compared with pure phase Ag2Se, the power factor will be reduced to varying degrees after Ag2Se is composited with amorphous Sb2S3 and crystalline Sb2S3; but the effect of amorphous Sb2S3 on the power factor is relatively small, and the power factor is only slightly reduced, while crystalline Sb2S3 will greatly reduce the power factor. This is because the main function of amorphous Sb2S3 in the present invention is to reduce thermal conductivity, and the thermoelectric properties of the composite material are optimized by reducing thermal conductivity. Even if amorphous Sb2S3 has a weak negative impact on the power factor, this is within an acceptable range. Therefore, from the perspective of the comprehensive performance of the composite material, the introduction of amorphous Sb2S3 has a positive impact on the thermoelectric material and optimizes the thermoelectric performance.

[0052] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a silver selenide-based composite room-temperature thermoelectric material, characterized in that: The following steps are involved: S1, preparing pure phase Ag2Se powder; S2, preparing amorphous nano-Sb2S3 powder; S3, preparing Ag2Se / Sb2(S,Se)3 composite thermoelectric material, comprising the following sub-steps: S31, ultrasonically dispersing pure Ag2Se powder in acidic water to form an Ag2Se dispersion; ultrasonically dispersing Sb2S3 powder in another portion of acidic water to form an Sb2S3 dispersion; S32, dropping the Ag2Se dispersion into the Sb2S3 dispersion under continuous ultrasonic conditions, and then mechanically stirring for 2-3 hours, and then standing to allow the powder to precipitate, collecting the precipitated powder and vacuum drying to obtain Ag2Se / Sb2S3 composite powder; S33. The Ag2Se / Sb2S3 composite powder is sintered into a block by spark plasma sintering at a sintering pressure of 45 MPa, a sintering temperature of 300-380°C, and a holding time of 5-7 min to finally obtain Ag2Se / Sb2(S,Se)3 composite thermoelectric material.

2. The method for preparing the silver selenide-based composite room temperature thermoelectric material according to claim 1, characterized in that: In step S31, the amount of Sb2S3 powder used accounts for 0.1-0.6% of the mass of pure phase Ag2Se powder.

3. The method for preparing the silver selenide-based composite room temperature thermoelectric material according to claim 1, characterized in that: In step S31, the acidic water used is an aqueous solution adjusted to pH=3.

4. The method for preparing the silver selenide-based composite room temperature thermoelectric material according to claim 1, characterized in that: In step S32, the vacuum drying temperature is 50-70°C, and the drying time is 20-24h.

5. The method for preparing the silver selenide-based composite room temperature thermoelectric material according to claim 1, characterized in that: Step S1: The method for preparing pure phase Ag2Se powder is as follows: S11, dissolving AgNO3 in ethylene glycol, adding Se powder, and stirring until the Se powder is evenly dispersed in the solution to obtain a dispersion; S12, add NaOH solution to the dispersion, stir evenly, heat to 200-250°C, and react for 24h; S13. After the reaction is completed, the solid product is collected by centrifugation, and the solid product is washed and vacuum dried to obtain pure Ag2Se powder.

6. The method for preparing the silver selenide-based composite room-temperature thermoelectric material according to claim 5, characterized in that: In step S11, the molar ratio of AgNO3 to Se powder is 2:

1.

7. The method for preparing the silver selenide-based composite room temperature thermoelectric material according to claim 1, characterized in that: The method for preparing amorphous nano-Sb2S3 powder in step S2 is as follows: S21. Dissolve SbCl3 in HCl solution to obtain solution A; dissolve Na2S·9H2O in NaOH solution to obtain solution B; S22. During continuous ultrasonic oscillation, solution B is slowly added dropwise to solution A, and ultrasonication is continued for 2 hours. The solid product is then collected by centrifugation, and further washed and dried to obtain amorphous nano-Sb2S3 powder.

8. The method for preparing the silver selenide-based composite room temperature thermoelectric material according to claim 7, characterized in that: In step S21, the molar ratio of SbCl3 to Na2S·9H2O is 2:

3.

9. A silver selenide-based composite room temperature thermoelectric material, characterized in that: The preparation method is adopted according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Energy storage device for high temperature applications

    CN116313543A

  • Method for preparing silver selenide / terpilenol flexible composite film with high thermoelectric performance

    CN117794345A

  • Preparation method of Ag2Se / AgXSe2 (X / Sb or Bi) thermoelectric composite material

    CN118234357A

  • Ag-se-based n-type thermoelectric material and flexible printed thermoelectric generator comprising the same

    EP3796404A1

  • Thermoelectric material element, power generator, light sensor, and method for manufacturing thermoelectric material element

    WO2019171915A1